Posterior interosseous nerve lesion due to lipoma. Review of the literature and rare case presentation - Rojc Bojan; Golob Peter (Radiology and Oncology)
Posterior interosseous nerve lesion is a rare mononeuropathy of the upper limb. Atraumatic posterior interosseous nerve lesions are commonly caused by lipomas of the forearm, manifesting as slow-progressing wrist and finger drop.